Effectiveness of Balance Training in Preventing Falls Among the Elderly: A Scoping Review - Salim, Catherine Hermawan; Dewi, Astrid Komala; Harahap, Sarah Geltri (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Introduction : The risk of falls among the elderly is a significant public health concern, impacting both quality of life and mortality rates. Balance training has been widely implemented as an intervention strategy to prevent falls; however, the effectiveness and variety of training methods remain diverse in the literature. Methods : This study is a scoping review conducted in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines. A comprehensive literature search was performed across PubMed, Scopus, Google Scholar, and the Cochrane Library using relevant keywords such as “balance training,” “fall prevention,” and “elderly.” Included studies were published between 2020 and 2025 and involved balance training interventions among older adults. Results : Out of 500 articles initially identified, 13 met the inclusion criteria. Balance training was shown to have a positive effect in reducing fall risk, improving postural control, and enhancing self-confidence among older adults in performing daily activities. The most commonly used interventions included Tai Chi, proprioceptive training, and multifunctional programs combining strength and balance exercises. Conclusion : Balance training is an effective intervention for fall prevention in the elderly. The success of such interventions depends on the regularity, intensity, and type of training applied. Further research is needed to standardize optimal training programs for older populations with varying levels of fall risk. Keywords : balance training, falls, elderly